Ecological validity and reliability of the rugby sevens simulation protocol - Furlan, N.; Waldron, M.; Osborne, M.; Gray, A. J. (International Journal of Sports Physiology and Performance, 2016)
To assess the ecological validity of the Rugby Sevens Simulation Protocol (R7SP) and to evaluate its interday reliability.